Geraldine Pu and her lunchbox, too! - Chang, Maggie P. (Chang, Maggie P. Geraldine Pu., 2021)
With encouragement from her supportive lunchbox, a young girl ignores a classmate's teasing and heartily enjoys bao buns, stinky tofu, and other tasty lunches prepared by her Taiwanese grandmother.